CAPD eBook: A multimedia approach for renal patients with adaptation of persuasive technology / Arifah Fasha Rosmani...[et al.] - Rosmani, Arifah Fasha; Shalahudin,, Nurul Fatahiyah; Ahmad, Siti Zulaiha; Rosmani, Anith Farhana (Universiti Teknologi MARA, Kedah, 2012)
CAPD eBook is a multimedia application that has been developed as a guide for renal patients on how to perform Continuous Ambulatory Peritoneal Dialysis (CAPD) in their daily life. The application has embraced multimedia elements such as text, animation, audio and graphic to ease renal patients in the learning process. This multimedia application is specifically designed to assist renal patients to learn and perform CAPD procedures as a way to remove toxin from their body. Additionally, the principle of Persuasive Technology has been adapted into CAPD eBook to increase effectiveness; this is to engage patients in using the application. Persuasive Technology is one of the techniques to persuade and encourage people in many aspects especially in the learning process. In order to evaluate the application, Usability and Heuristic Test have been conducted to assess the convenience and significance of Persuasive Technology Principles in CAPD eBook. The results have shown a significant impact and important benefits provided to renal patients.